ZIF‐induced d‐band modification in a bimetallic nanocatalyst : achieving over 44 % efficiency in the ambient nitrogen reduction reaction - Sim, Howard Yi Fan (2021)
The electrochemical nitrogen reduction reaction (NRR) offers a sustainable solution towards ammonia production but suffers poor reaction performance owing to preferential catalyst–H formation and the consequential hydrogen evolution reaction (HER). Now, the Pt/Au electrocatalyst d-band structure is electronically modified using zeolitic imidazole framework (ZIF) to achieve a Faradaic efficiency (FE) of > 44% with high ammonia yield rate of > 161 mgmgcat @1 h @1 under ambient conditions. The strategy lowers electrocatalyst d-band position to weaken H adsorption and concurrently creates electron-deficient sites to kinetically drive NRR by promoting catalyst–N2 interaction. The ZIF coating on the electrocatalyst doubles as a hydrophobic layer to suppress HER, further improving FE by > 44-fold compared to without ZIF (ca. 1%). The Pt/Au-NZIF interaction is key to enable strong N2 adsorption over H atom.